Interpretation of friction and wear in DLC film: role of surface chemistry and test environment. (7th October 2016) - Polaki, S R; Kumar, N; Madapu, K; Ganesan, K; Krishna, N G; Srivastava, S K; Abhaya, S; Kamruddin, M; Dash, S; Tyagi, A K
Abstract: In spite of the large amount of tribological work carried out to explain the friction and wear mechanism in diamond-like carbon (DLC) films, some of the core issues relating to the evolution of reactive species across sliding interfaces and their role on the friction and wear mechanism remain unclear. The phase composition, film density and hydrogen content present in a DLC film can be tailored by substrate biasing during film deposition to achieve a nearly vanishing friction coefficient. Furthermore, nitrogen doping in DLC films significantly improves wear resistance, and sliding occurs in a nearly wearless regime. Undoped and nitrogen-doped DLC films exhibit a nearly frictionless value with ultra-low wear behavior when tests are performed in argon, nitrogen and methane atmospheres. The antifriction and antiwear properties of the DLC films were improved with the reduction of adsorbed oxygen impurities on the film surface. This behavior was understood by correlating the oxygen impurities present at the surface/subsurface region of the DLC film while using x-ray photoelectron spectroscopy and depth-resolved Auger electron spectroscopy.